Breathe Easy, Speak Easy: Pulmonary Function and Language Performance in Aging. Issue 5 (20th October 2018) - Cahana-Amitay, Dalia; Lee, Lewina, O.; Spiro, Avron; Albert, Martin L.
ABSTRACT: Background : This study explored the association between pulmonary function (PF) and older adults' language performance accuracy. Study rationale was anchored in aging research reporting PF as a reliable risk factor affecting cognition among the elderly. Methods : 180 adult English native speakers aged 55 to 84 years participated in the study. PF was measured through forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), and FEV1/FVC ratio (FFR). Language performance was assessed with an action naming test and an object naming test, and two tests of sentence comprehension, one manipulating syntactic complexity and the other, semantic negation. Greater PF was predicted to be positively associated with all tasks. Results : Unadjusted models revealed FVC and FEV1 effects on language performance among older adults. Participants with higher FVC showed better naming on both tasks and those with higher FEV1 had better object naming only. In covariate-adjusted models, only a positive FVC-object naming association remained. Conclusion : Findings were discussed in terms of brain oxygenation mechanisms, whereby good PF may implicate efficient oxygenation, supporting neurotransmitter metabolism that protects against neural effects of cerebrovascular risk. Effects on object naming were linked to putative differential oxygenation demands across language tasks.